Local Anaesthetic Myotoxicity Due to Fascial Plane Blocks: A Brief Review - Abhijit S Nair (Global Journal of Anesthesiology - Peertechz Publications, 2017)
Fascial plane blocks have become quite popular in the present practice of regional anaesthesia. Transverses abdominal plane (TAP) block, quadratus lumborum (QL), serratus anterior plane (SAP) block, pectoralis block (PECS 1/ 2), rectus sheath and adductor canal block are quite easy to perform with ultrasonographic (USG) guidance. The anaesthesiologist identifies the muscles and the relevant fascial plane to inject the local anaesthetic (LA) in the desired plane under USG guidance. Current prospective and observational studies have shown that these are quite effective as a single injection and can be used for continuous analgesia with an indwelling catheter in the fascial plane. All fascial plane blocks are transmuscular injections i.e. the needle has to reach the target plane by piercing the adjoining muscles. There are high chances of LA injection in the muscle or spillage of LA in the substance of muscle especially after high volume LA injections. The possibility is more when an anaesthesiologist has recently learnt a fascial plane block and is applying it in clinical practice. The myotoxicity could be more profound in continuous LA infusions where the muscle will get continuously exposed to LA.